Amita Baviskar. Uncivil City: Ecology, Equity and the Commons in Delhi. 2020, Sage and Yodapress. (The Pakistan Development Review, 2021)
Amita Baviskar’s latest book titled Uncivil City: Ecology, Equity and the Commons in Delhi provides an in-depth analysis of exclusion of the Commons from the socio-economic and political spaces of inarguably India’s most powerful city; Delhi. The book is divided into three sections with eights chapters encompassing book’s themes. It starts with setting the context by explaining the reasons for titling the book as ‘Uncivil City’. Conceptualising Delhi as Uncivil expounds the City’s changing spatial dynamics which the author has detailed by analysing City’s social history by doing socio-historical analysis. She also reminisces her early-life experiences with the City; what the City was for the Commons in the past; how infrastructural development has excluded the Commons; what the City’s formal politics and politicised environment is doing to the Commons and what does future entail for them.